(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2026)
In order to develop recommendations for prosthetics in patients suffering from epilepsy, a study of the condition of existing prostheses was conducted, and the existing prosthetic protocols for such patients were studied. It was revealed that when prosthetizing such patients, they adhere to the prosthetics protocols of somatically healthy patients, and the condition of existing prostheses is recognized as unsatisfactory and has indications for replacement.